Welcoming the Stranger: Anatheism and L'Arche - Little, Brent (Toronto journal of theology, 2016)
In his book Anatheism, Richard Kearney argues for God to be imagined as a stranger and a guest, a God who comes unexpectedly into mundane reality. As a potential host, the human person may freely say yes in hospitality or no in hostility to this divine stranger, a hospitality or hostility practised in encounters with the everyday strangers of life, such as marginalized populations. As an exemplar, Kearney offers Jean Vanier's vision for L'Arche, a global network of communities that live in solidarity with the developmentally disabled. But Kearney provides only a start for a theological dialogue with L'Arche's experience. In order to further refine this conversation between Kearney and L'Arche, I consider questions about the limits of hospitality in the context of L'Arche. What are, for example, necessary boundaries between guest and host? When does uncritical hospitality become problematic? After a discussion of Kearney's anatheism and the writings of Vanier, Henri Nouwen, and others, I argue for the necessity of judiciously drawn boundaries so as to promote a healthy relationship between the disabled person and the assistant, a relationship that hopefully has become one of friendship. This article, then, confronts the task of discerning the limits to Kearney's paradigm, and L'Arche's practice, of hospitality.